1999
DOI: 10.1074/jbc.274.41.28900
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor Down-regulation

Abstract: Sustained activation of most G protein-coupled receptors causes a time-dependent reduction of receptor density in intact cells. This phenomenon, known as downregulation, is believed to depend on a ligand-promoted change of receptor sorting from the default endosomeplasma membrane recycling pathway to the endosomelysosome degradation pathway. This model is based on previous studies of epidermal growth factor (EGF) receptor degradation and implies that receptors need to be endocytosed to be down-regulated.In sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 54 publications
6
44
2
Order By: Relevance
“…42). The cleavage site within the ␤ 2 -adrenergic receptor has not been determined (43). In case of the TSH receptor, spontanous release of the highly glycosylated extracellular N terminus was observed (44).…”
Section: The [⌬2-64]et B -Gfp Fusion Protein Shows Normal Et1-inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…42). The cleavage site within the ␤ 2 -adrenergic receptor has not been determined (43). In case of the TSH receptor, spontanous release of the highly glycosylated extracellular N terminus was observed (44).…”
Section: The [⌬2-64]et B -Gfp Fusion Protein Shows Normal Et1-inducedmentioning
confidence: 99%
“…The ligand-dependence of this process favor the involvement in receptor activation or down-regulation. However, the proteolysis does not destroy receptor function and the overall structure, as is the case for the vasopressin V 2 receptor or the ␤ 2 -adrenergic receptor (42,43). Rather it generates a new N terminus, similar to the PAR family, although the new N terminus (SLAPAE) of the ET B receptor does not share sequence similarity with that of the of PAR1, PAR2, and PAR4 receptors (SFLLRN/TFLLR, SLIGRL, and GYPGKF, respectively).…”
Section: The [⌬2-64]et B -Gfp Fusion Protein Shows Normal Et1-inducedmentioning
confidence: 99%
“…In one study proteasomal but not lysosomal inhibitors reduced the down-regulation of and ␦ opioid receptors (14), whereas in another, lactacystin, a very specific proteasomal inhibitor, did not impair agonist-induced internalization, lysosomal targeting, and degradation of the ␦ opioid receptor (15). Some of these studies found that steadystate receptor levels increase in unstimulated cells treated with proteasomal inhibitors (14,17). The presence of proteasomal inhibitors also enhances the ubiquitination of some GPCRs (14,16).…”
mentioning
confidence: 96%
“…E-64 and leupeptin inhibit lysosomal cysteine proteases, and leupeptin also inhibits serine proteases (32). ALLN, MG132, and lactacystin block proteasomal activity, with lactacystin having the greatest specificity (17). Degradation of ␤ 1 AR expressed in BHK and HEK 293 cells was determined using the surface biotinylation procedure described above.…”
Section: ␤ 1 Ar Resistance To Agonist-mediated Down-regulation In Hekmentioning
confidence: 99%
See 1 more Smart Citation